ṭʿnt "ṭmʾh ʾny lkh" / On the Claim "I am Forbidden to You" - Kohen, ʿAmiḥai (Hebrew Union College annual, 2008)
The last mishnah in Nedarim deals with a priest's wife who declares that she has been defiled, thus prohibited from remaining married to her husband. The mishnah describes the revision that halakhah underwent regarding this claim: from a period when the wife's claim was accepted and the husband forced to divorce her, to concluding that the wife's contention should be proven — fearing she preferred another man. The post-talmudic discussions are characterized by linking the issue of "I have become defiled" to the wife's claim, "My husband is repugnant to me" and the husband's claim, "You have become defiled." A review of the codes and responsa literature reveals many opinions, difficulties, and unanswered questions. This article endeavors to create a judicial model based on the assumption that the woman's claim, "I have become defiled" is regarded as "self-incrimination." This model can clarify the mishnah's two strata, opinions of different commentaries, the geonim's different attitudes, and those of some of the rishonim to the claim, "I have become defiled," in contrast to their view regarding the claim, "My husband is repugnant to me," and the different attitudes of various adjudicators to the husband's claim, "You have become defiled."